(3GdYbjOI GdeajOI YbjOI GdSda hCUMGH GdMOjKs - (3CHh YKeGf ESeGYjd Hf YHO GdQMef GdUCHhfjs ((3YHO GdYRjR Hf YHO Gddg Hf eMeO Hf SdjeGf Hf YGeQ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO aEfi deG hQOJ BeO WHQSJGf hHdGO LjdGf eJhLgkG Edi HjJ Gddg GdMQGe SFdfi ENhGfi ai GdOjf Cf GLeY dge aUhdkG ai CUhd GdOjf s
(3BNQgG (B:s
(3aMOKg HMOjK CHj gQjQI EMJL Be hehSi abGd YjSi Hf LYaQ cja gPG hHfj i(B>(3e hehSi eG HjfgeG hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3Ydi UaMI GdYfhGf JQLeI ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds